Optimization of Limestone Production Based on Geological Structure Conditions for Blasting Geometry Design - Fachrur Reza Assegaff; Cipta Endayana; Nana Sulaksana; Dwi Putranto Waloeyo (Pusat Survei Geologi, 2020)
The research location is in Sumber Arum, a village in Kerek District, Tuban Regency, East Java. The object of this study includes the state of the geological structure around the mining site and its effect on blasting activities. The purpose of this study is to obtain a blasting geometry design that is suitable for the geological structure conditions at the mining site so that the resulting blasting fragmentation has a uniform size to increase the amount of company production. The method used in this study is to combine data from measurements and observations in the field with blasting design theory. From these data, further analysis and trial blasting activities are conducted and the results obtained from the actual blasting plan with the proposed blasting plan are compared. The calculation results of the blasting geometry design obtained the proposed blasting geometry values, including the burden of 2.5 meters, the spacing of 3 meters, the stemming of 1.75 meters, the subdrilling of 0.5 meters, the shot hole depth of 6.5 meters, and the direction of the explosion of 6.5 meters that is located at point N37ÂºE. Based on the application, the blasting fragmentation with a size of â‰¤ 80 cm is evenly distributed, with a percentage of 99.44% of the total fragmentation resulting from blasting. The amount of limestone produced in one year is 20.138.946 tons.Keywords: blasting geometry, production, limestone, geological structure